2021
DOI: 10.3390/su13126836
|View full text |Cite
|
Sign up to set email alerts
|

Resilience Dynamic Assessment Based on Precursor Events: Application to Ship LNG Bunkering Operations

Abstract: The focus of the present paper is the development of a resilience framework suitable to be applied in assessing the safety of ship LNG (Liquefied Natural Gas) bunkering process. Ship propulsion considering LNG as a possible fuel (with dual fuel marine engines installed on board) has favored important discussions about the LNG supply chain and delivery on board to the ship power plant. Within this context, a resilience methodological approach is outlined, including a case study application, to demonstrate its a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Resilience assessment of CINs can help decision-makers improve safety strategies and reduce resources required for post-disaster recovery [29,30]. However, research on OPNS resilience is rarely reported [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…Resilience assessment of CINs can help decision-makers improve safety strategies and reduce resources required for post-disaster recovery [29,30]. However, research on OPNS resilience is rarely reported [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…Some research studies have been conducted regarding the risks of LNG bunkering. These have mainly focused on the following three aspects: (1) safety zone evaluation [10][11][12][13][14][15][16][17][18][19][20][21][22], (2) risk assessment methodology and practice [23][24][25][26][27], and (3) emergency evacuation assessment [27,28]. Even though these studies have improved our understanding of LNG bunkering safety, none has quantified human errors in LNG bunkering.…”
Section: Introductionmentioning
confidence: 99%
“…(2) risk assessment methodology and practice [23][24][25][26][27], and (3) emergency evacuation assessment [27,28]. Even though these studies have improved our understanding of LNG bunkering safety, none has quantified human errors in LNG bunkering.…”
Section: Introductionmentioning
confidence: 99%